2023
DOI: 10.3389/fpsyg.2022.999130
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional analysis of yoga experience on variables associated with psychological well-being

Abstract: IntroductionPrevious research has identified numerous physical, psychological, and spiritual benefits associated with the practice of yoga. Indeed, yoga has been linked with improved quality of life, reduced stress, and numerous markers of psychological well-being. In the current research, a cross-sectional design was used to examine whether the psychological benefits associated with yoga only apply to long-term practitioners or whether more “casual,” intermittent yoga experience could produce positive outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
(82 reference statements)
0
0
0
Order By: Relevance
“…Participants demonstrated improved abilities to recognize body sensations, manage attention, become more emotionally aware, engage in self-regulation, listen to their bodies, and establish trust in their bodily experiences. These findings are consistent with previous research that has found that MM practices, such as yoga and tai chi, improve interoceptive awareness (69)(70)(71) and could be interesting in the light of the known relationship between interoceptive awareness and emotional regulation (72,73).…”
Section: Discussionsupporting
confidence: 92%
“…Participants demonstrated improved abilities to recognize body sensations, manage attention, become more emotionally aware, engage in self-regulation, listen to their bodies, and establish trust in their bodily experiences. These findings are consistent with previous research that has found that MM practices, such as yoga and tai chi, improve interoceptive awareness (69)(70)(71) and could be interesting in the light of the known relationship between interoceptive awareness and emotional regulation (72,73).…”
Section: Discussionsupporting
confidence: 92%